1997
DOI: 10.1007/s002640050180
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors in degenerative spondylolisthesis

Abstract: Summary. We report a prospective study analysing whether possible factors predisposing to degenerative spondylolisthesis (DS) must be present concomitantly in order to cause vertebral slipping. Standard and flexion-extension radiographs were obtained from 27 patients with DS and 27 without spondylolisthesis. The level of the intercrestal line, the lumbosacral angle, the presence of sacralization of L5 and vertebral motion at the L4 ± L5 level were assessed. Facet joint orientations were measured on CT scans. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 26 publications
(36 reference statements)
1
49
0
1
Order By: Relevance
“…Showing the difference of the facet joint angle between patients with degenerative spondylolisthesis and controls, Sato et al [18] have stated that individuals with sagittal facet joints are candidates for degenerative spondylolisthesis. Other investigators [3,5,11,14,16] had similar findings in their studies, some of which included normal control subjects. However, the ages of patients with degenerative spondylolisthesis and the control subjects were not matched so the judgement might be biased.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Showing the difference of the facet joint angle between patients with degenerative spondylolisthesis and controls, Sato et al [18] have stated that individuals with sagittal facet joints are candidates for degenerative spondylolisthesis. Other investigators [3,5,11,14,16] had similar findings in their studies, some of which included normal control subjects. However, the ages of patients with degenerative spondylolisthesis and the control subjects were not matched so the judgement might be biased.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, some studies have suggested an association between sagittal alignment of the facet joint and degenerative spondylolisthesis [3,5,9,11,14,16,18]. However, the role of facet tropism in degenerative spondylolisthesis is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…No difference has been reported in the incidence of spondylolysis or spondylolisthesis between patients with LSTVs and controls. 2,5,10,46 It has been observed that in patients with lytic spondylolisthesis, there is a greater degree of slip seen at the L4 -5 level above an L5 transition compared with the L5-S1 level above an S1 transition. 47 Connolly et al, 17 in a series of 48 patients with low back pain and an LSTV, showed increased uptake at the anomalous articulation between the transverse process of the LSTV and the sacrum in 81% of patients.…”
Section: Fig 11mentioning
confidence: 99%
“…A relationship between transitional vertebrae and the degree of slippage in spondylolytic spondylolisthesis has been 19,26 established.…”
Section: )mentioning
confidence: 99%